PGE2‐EP3 axis promotes brown adipose tissue formation through stabilization of WTAP RNA methyltransferase. (4th July 2022) - Tao, Xixi; Du, Ronglu; Guo, Shumin; Feng, Xiangling; Yu, Tingting; OuYang, Qian; Chen, Qiaoli; Fan, Xutong; Wang, Xueqi; Guo, Chen; Li, Xiaozhou; Xue, Fengxia; et al.
Abstract: Brown adipose tissue (BAT) functions as a thermogenic organ and is negatively associated with cardiometabolic diseases. N 6 ‐methyladenosine (m 6 A) modulation regulates the fate of stem cells. Here, we show that the prostaglandin E2 (PGE2 )–E‐prostanoid receptor 3 (EP3) axis was activated during mouse interscapular BAT development. Disruption of EP3 impaired the browning process during adipocyte differentiation from pre‐adipocytes. Brown adipocyte‐specific depletion of EP3 compromised interscapular BAT formation and aggravated high‐fat diet‐induced obesity and insulin resistance in vivo . Mechanistically, activation of EP3 stabilized the Zfp410 mRNA via WTAP‐mediated m 6 A modification, while knockdown of Zfp410 abolished the EP3‐induced enhancement of brown adipogenesis. EP3 prevented ubiquitin‐mediated degradation of WTAP by eliminating PKA‐mediated ERK1/2 inhibition during brown adipocyte differentiation. Ablation of WTAP in brown adipocytes abrogated the protective effect of EP3 overexpression in high‐fat diet‐fed mice. Inhibition of EP3 also retarded human embryonic stem cell differentiation into mature brown adipocytes by reducing the WTAP levels. Thus, a conserved PGE2 ‐EP3 axis promotes BAT development by stabilizing WTAP/Zfp410 signaling in a PKA/ERK1/2‐dependent manner. Synopsis: Development of brown adipose tissue (BAT) is tightly regulated by transcriptional and epigenetic reprogramming, but its upstream regulation remains poorly understood. Here, prostaglandin receptor signalling is shown to be a key promoter of brown adipogenesis enhancing expression of thermogenic gene programs. The PGE2 /EP3 axis is activated during the development of interscapular BAT in mice. BAT‐specific depletion of EP3 results in adipocyte whitening and aggravated diet‐induced obesity. Loss of EP3 accelerates ubiquitin‐mediated degradation of N6‐methyladenosine methyltransferase WTAP, decreasing m 6 A‐dependent mRNA stability of brown gene transcription factor Zfp410. EP3 receptor‐mediated control of brown adipogenesis is conserved in human embryonic stem cell differentiation. Abstract : Prostaglandin receptor signaling safeguards brown adipose tissue differentiation via ERK‐and mRNA modification‐dependent control of thermogenic gene programs.